2003
DOI: 10.1074/jbc.m204411200
|View full text |Cite
|
Sign up to set email alerts
|

Role of Protein Kinase CK2 Phosphorylation in the Molecular Chaperone Activity of Nucleolar Protein B23

Abstract: Protein B23 is a multifunctional nucleolar protein whose molecular chaperone activity is proposed to play role in ribosome assembly. Previous studies (Szebeni, A., and Olson, M. O. J. (1999) Protein Sci. 8, 905-912) showed that protein B23 has several characteristics typical of molecular chaperones, including anti-aggregation activity, promoting the renaturation of denatured proteins, and preferential binding to denatured substrates. However, until now there has been no proposed mechanism for release of a boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
79
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 31 publications
(41 reference statements)
1
79
0
Order By: Relevance
“…Recent studies show that NPM phosphorylation by CKII is involved in ribosome biogenesis by increasing its binding affinity to other nucleolar components as well as positively regulating nuclear import of proteins. Phosphorylation by CKII enhances NPM's affinity to the NLS sequences derived from the SV40 large T antigen and HIV Rev protein [13,46], as well as modulating its molecular chaperoning activity, especially for its interaction with target proteins [47]. In this study, NPM phosphorylated with a cdc2-like protein kinase or mutant forms of NPM in which the nuclear localization signal is either deleted or altered do not stimulate nuclear import of the substrates.…”
Section: Npm Phosphorylationmentioning
confidence: 94%
“…Recent studies show that NPM phosphorylation by CKII is involved in ribosome biogenesis by increasing its binding affinity to other nucleolar components as well as positively regulating nuclear import of proteins. Phosphorylation by CKII enhances NPM's affinity to the NLS sequences derived from the SV40 large T antigen and HIV Rev protein [13,46], as well as modulating its molecular chaperoning activity, especially for its interaction with target proteins [47]. In this study, NPM phosphorylated with a cdc2-like protein kinase or mutant forms of NPM in which the nuclear localization signal is either deleted or altered do not stimulate nuclear import of the substrates.…”
Section: Npm Phosphorylationmentioning
confidence: 94%
“…Overexpression and tumorigenic activation of the Smoothened (SMO) protooncogene mediates c-myc overexpression, suggesting that SMO may also be a prognostic factor in HCC tumorigenesis (Sicklick et al, 2006). Nucleophosmin (NPM) is a major nucleolar phosphoprotein implicated in multiple cellular functions, including ribosomal protein assembly and transport (Verheggen et al, 2000;Huang et al, 2005), centrosome duplication (Okuda et al, 2000;Okuda, 2002;Grisendi et al, 2005), molecular chaperone activity in preventing protein aggregation (Hingorani et al, 2000;Szebeni et al, 2003), and regulating the activity of the tumour suppressors p53 (Colombo et al, 2002;Li et al, 2004;Maiguel et al, 2004) and p14 ARF (Itahana et al, 2003;Bertwistle et al, 2004;Brady et al, 2004). Earlier studies have shown that the level of NPM is markedly and promptly increased in association with cell commitment to mitogenesis (Feuerstein and Mond, 1987;Feuerstein et al, 1988).…”
mentioning
confidence: 99%
“…To determine whether B23 compartmentation depends on its phosphorylation by CK2, B23 mutants were used ( Figure 6A). In the B23 sequence, serine 125 is the main site of CK2 phosphorylation (Szebeni et al, 2003). The GFP-tagged B23 protein containing the amino acid substitution S125 to alanine (GFP-B23-S125A) is recruited into the nucleolus ( Figure 6B, a and aЉ).…”
mentioning
confidence: 99%
“…The effect of CK2 alone on nucleolar reformation was not significant except for a slight increase in the number of compact nucleoli (compare Figure 5, c and d, with Figure 3b). We next examined nucleolar reformation after addition of CK2 (Okuwaki et al, 2002); S125A corresponds to the substitution mutation S125 by alanine in the region of the sequence containing the CK2-binding site (Szebeni et al, 2003); and T199A corresponds to the substitution mutation T199 by alanine (Tokuyama et al, 2001). Arrows point to the major phosphorylation sites in B23 domains: black box corresponds to the acidic region, the gray box to RNase activity, and the striped box to RNA binding activity (Hingorani et al, 2000).…”
mentioning
confidence: 99%